2016
DOI: 10.1371/journal.pone.0166258
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Occurrence of Trichinella-Specific Antibodies in Domestic Pigs in Central and Eastern Uganda

Abstract: Previous research on trichinellosis in Africa focused on isolating Trichinella from wildlife while the role of domestic pigs has remained highly under-researched. Pig keeping in Uganda is historically recent, and evidence on zoonotic pig diseases, including infection with Trichinella species, is scarce. A cross-sectional survey on Trichinella seroprevalence in pigs was conducted in three districts in Central and Eastern Uganda from April 2013 to January 2015. Serum from a random sample of 1125 pigs from 22 vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…surveillance in pigs, according to the International Commission on Trichinellosis [ 7 ]. Since serology has been shown to occasionally yield false-positive results, or sometimes positive results with very low to undetectable levels of larval burden [ 4 , 23 ], it would be warranted that any seropositive pig be further confirmed by the artificial digestion assay. A study to evaluate the reproducibility and validation of an ELISA has shown that, when the recommended protocol is strictly followed, a negative result is an excellent indicator of the absence of infection, with a specificity of 98.29% [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…surveillance in pigs, according to the International Commission on Trichinellosis [ 7 ]. Since serology has been shown to occasionally yield false-positive results, or sometimes positive results with very low to undetectable levels of larval burden [ 4 , 23 ], it would be warranted that any seropositive pig be further confirmed by the artificial digestion assay. A study to evaluate the reproducibility and validation of an ELISA has shown that, when the recommended protocol is strictly followed, a negative result is an excellent indicator of the absence of infection, with a specificity of 98.29% [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the seroprevalence of Trichinella infection from pig muscle samples was 10.9% compared to 10.8% obtained in warthogs. Serological studies implemented in pigs in Egypt, Nigeria, and Uganda reported seroprevalence of 4.5%, 40%, and 6.9%, respectively [17][18][19]. This difference in prevalence observed could be due to the management mode of the different farms and the hygiene applied.…”
Section: Discussionmentioning
confidence: 96%
“…However, a high prevalence of porcine and human cysticercosis has been reported (44)(45)(46), as well as non-typhoidal Salmonella isolates which were recovered from pig faecal samples (47). In neighbouring countries, trichinellosis, salmonellosis, and cysticercosis have been documented in pigs (48)(49)(50)(51)(52) and in humans (53,54).With the exception of the single modern abattoir, slaughter houses had intercrossing of clean and dirty operations, from killing through to carcass preparation. This is likely to lead to cross-contamination with pathogens such as Salmonella (55), especially as no running water was available inside the visited slaughterhouses, as has been reported elsewhere (49).…”
Section: Discussionmentioning
confidence: 99%